Implementasi Profile Matching Pada Penerimaan Bantuan Langsung Tunai - Ginting, Erwin; Tambunan, Frinto; Nurhayati, Nurhayati; Fauzi, Muhammad (TIN: Terapan Informatika Nusantara, 2021)
Various problems arise when direct cash assistance from the government which is carried out in each region begins to be disbursed to people who are entitled to it. One of them is the error in selecting the target recipient of assistance, according to the regulations, residents who receive assistance must comply with applicable conditions such as Indonesian citizens, the poor, the elderly and affected by COVID-19, but there are still people who are classified as capable of being able to get the BLT due to the accumulation of data. numbered in the thousands and packaged in a manual system resulting in assistance not being channeled to the right people, with this problem the author took the initiative to create a system that was implemented with the profile matching method with criteria taken from the data on the requirements for receiving BLT from the government to provide solutions to problems by determining residents appropriate and appropriate in receiving the cash direct assistance. Data research was carried out using the prototyping concept to increase the accuracy of receiving cash transfers that were processed with a decision support system to facilitate the acceptance process so that it was more accurate and faster and did not harm related parties. This system is designed in such a way that it can be accessed by the general public and with Android devices to facilitate the admissions selection process.